Analisis Kualitas Pelayanan Publik di Kantor Camat Ladongi Kabupaten Kolaka - . Jamal (e-JKPP, 2015)
Problem of this research that is : ( 1) What will be public service quality in Office of Subdistrict of Ladongi of Regency Kolaka? (2) Factors of what pursuing public service quality in Office of Subdistrict of Ladongi of Regency Kolaka? Pursuant to background of problem and research target, hence this research approach use the research type qualitative with the descriptive analysis method. All data obtained is direct the than informan in field by using data interview conducted by through informal interview and structure do not by utilizing guidance interview as hold and observation.Pursuant to research result, that service in Office of Subdistrict of Ladongi of Regency Kolaka, have been executed properly, but its result not yet optimal, this matter is menunjukan that officer attitude not yet full improve the service quality in Office of Subdistrict of Ladongi of Regency Kolaka, according to service dimension that is : (1) Human Resource Ability, relative the lack of ability, resulting less be its his optimal is officer in running public service (2) column Freshment in course of service, in Office of Subdistrict of Ladongi of Regency Kolaka, relative facility less so that society managing letter in Office of Subdistrict Ladongi feel less be balmy, (3) service Quality of Office of Subdistrict of Ladongi of Regency kolaka, not yet been conducted maximally by entangling all aparat, but only entangle the certain people, so that this matter make [do] not all aparat own the initiative to submit the suggestion and or idea as input in course of service in order to make-up of service quality.